Prerequisites for Public Acceptance of Waste-to-Energy Plants: Evidence from Germany and Indonesia - Lahl, Uwe; Zeschmar-Lahl, Barbara (UI Scholars Hub, 2018)
Construction of waste incinerators often encounters resistance from the public. The minimum requirements for the ac- ceptance of these installations include modern air pollution control (APC) technology and safe disposal of residues. Confidence in the statements of government and government agencies as well as on those who support is an important point of acceptance. Independent scientific bodies such as universities can help to make this happen. In the case of the installation of waste into energy (WtE), such scientific support can be the measurement of emissions and their evalua- tion. Many products that enter the waste stream contain heavy metals, persistent organic pollutants, and other harmful substances. Their presence constitutes another challenge for recycling. This challenge can be solved most likely by binding specifications for chemicals in and design for recycling of products.